Prevalence of mastitis and antimicrobial resistance patterns of Escherichia coli and Staphylococcus aureus isolated from the infected udder of dairy cows in coastal regions (Bangladesh Veterinarian, 2024)
Prevalence of mastitis and their antimicrobial resistance in Amtali (sub-district) area of Barguna District were studied. Mastitis was diagnosed by examining the udder and milk of 300 dairy cows. The bacteria were cultured and biochemical tests and antimicrobial profiling were done. The overall prevalence of mastitis was 5.0%, and cross-bred and local cows had 6.4% and 3.8%, respectively. The prevalence was higher in animals 7 - 8 years old (5.9%) and in cows of 3rd - 4th parity (8.8%). Cows with peri-parturient diseases and 1st - 2nd lactation had prevalence of 6.8% (P